It Takes a Mouth to Eat and a Nose to Breathe: Abnormal Oral Respiration Affects Neonates' Oral Competence and Systemic Adaptation - Marie Trabalon; Benoist Schaal (International Journal of Pediatrics)
Mammalian, including human, neonates are considered to be obligate nose breathers. When constrained to breathe through their mouth in response to obstructed or closed nasal passages, the effects are pervasive and profound, and sometimes last into adulthood. The present paper briefly surveys neonates' and infants' responses to this atypical mobilisation of the mouth for breathing and focuses on comparisons between human newborns and infants and the neonatal rat model. We present the effects of forced oral breathing on neonatal rats induced by experimental nasal obstruction. We assessed the multilevel consequences on physiological, structural, and behavioural variables, both during and after the obstruction episode. The effects of the compensatory mobilisation of oral resources for breathing are discussed in the light of the adaptive development of oromotor functions.